2009
DOI: 10.1097/ajp.0b013e3181b12dd3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Migraine Patients With and Without Allodynic Symptoms

Abstract: Allodynic symptoms occurred in 57.1% patients with migraine. In allodynic patients with moderate-to-severe headache, rizatriptan resulted in greater pain relief compared with ibuprofen. These results need further confirmation in larger study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 8 publications
1
21
0
1
Order By: Relevance
“…The relevance of our finding is not contradicting the notion that headache is the principal trigeminal pain in migraine. Nonetheless, an extensive clinical study carried out on 1,413 patients has indicated that, during an attack of migraine, the majority of them suffer from allodynia affecting the entire trigeminal territory [63], a finding confirmed to be independent from the presence of aura [64].…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of our finding is not contradicting the notion that headache is the principal trigeminal pain in migraine. Nonetheless, an extensive clinical study carried out on 1,413 patients has indicated that, during an attack of migraine, the majority of them suffer from allodynia affecting the entire trigeminal territory [63], a finding confirmed to be independent from the presence of aura [64].…”
Section: Discussionmentioning
confidence: 99%
“…The abnormalities in the brainstem aminergic pathway are well documented in migraine and these influence the neuronal excitability of the cortical neurons. 4,24 This may indirectly suggest that the anti-inflammatory drugs may be capable of reducing sensitization of the cortical neurons. 23 Nonsteroidal anti-inflammatory drugs are effective in both allodynic and nonallodynic migraineurs, 4 whereas triptans are more effective in nonallodynic patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The checklist of allodynia triggers was administered in which combing, fan air, shower, shaving, laying head on pillow, wearing necklace, necktie, ornaments, scarf, and veil were enquired. The duration of migraine, distribution and frequency of headache, migraine triggers, and family history of headache were noted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On at least eight days, the headache features should be of a migraine headache and the pain possibly relieved by a triptan or ergot derivative 3 . Cutaneous allodynia, a risk factor for chronic migraine 4 , increases the discomfort and disability of patients with acute migraine attacks 5 and is recognized as a clinical manifestation of central sensitization in migraine patients 6 . Cutaneous allodynia is defined as the perception of pain or discomfort in response to innocuous thermal (heat or cold) and/or mechanical (static or dynamic) stimuli applied to normal skin 6 .…”
mentioning
confidence: 99%